Hunting Eve - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2013)
Forensic sculptor Eve Duncan battles her captor -- the madman Jim Doane -- and discovers brutally dangerous truths about why she has been targeted.